Maximal heart rate does not limit cardiovascular capacity in healthy humans: insight from right atrial pacing during maximal exercise. (2nd December 2013) - Munch, G. D. W.; Svendsen, J. H.; Damsgaard, R.; Secher, N. H.; González‐Alonso, J.; Mortensen, S. P.
Abstract : Key points: During high intensity whole‐body exercise, systemic and contracting skeletal muscle O2 delivery and uptake ( V ̇ O 2 ) are compromised, but the underlying mechanisms remain unclear. We evaluated the effect of a ∼20 beats min −1 increase in heart rate (HR) by right atrial pacing during incremental cycling and knee‐extensor exercise on cardiac output ( Q ̇ ) and stroke volume (SV). An increase in HR during both exercise modalities did not alter Q ̇ due to a proportional decrease in SV. The lower SV during atrial pacing in the cycling trial was associated with a diminished cardiac filling pressure, but similar arterial pressure. The results demonstrate that the human heart can achieve a higher HR than observed during maximal exercise, suggesting that HRmax and myocardial work capacity do not limit cardiac performance in trained human subjects. Instead, restrictions in ventricular filling appear to compromise cardiac preload, SV and Q ̇ at exercise intensities close to V ̇ O 2 max . Abstract: In humans, maximal aerobic power ( V ̇ O 2 max ) is associated with a plateau in cardiac output ( Q ̇ ), but the mechanisms regulating the interplay between maximal heart rate (HRmax ) and stroke volume (SV) are unclear. To evaluate the effect of tachycardia and elevations in HRmax on cardiovascular function and capacity during maximal exercise in healthy humans, 12 young male cyclists performed incremental cycling and one‐legged knee‐extensor exercise (KEE) to exhaustion with and without right atrial pacing to increase HR. During control cycling, Q ̇ and leg blood flow increased up to 85% of maximal workload (WLmax ) and remained unchanged until exhaustion. SV initially increased, plateaued and then decreased before exhaustion ( P < 0.05) despite an increase in right atrial pressure (RAP) and a tendency ( P = 0.056) for a reduction in left ventricular transmural filling pressure (LVFP). Atrial pacing increased HRmax from 184 ± 2 to 206 ± 3 beats min −1 ( P < 0.05), but Q ̇ remained similar to the control condition at all intensities because of a lower SV and LVFP ( P < 0.05). No differences in arterial pressure, peripheral haemodynamics, catecholamines or V ̇ O 2 were observed, but pacing increased the rate pressure product and RAP ( P < 0.05). Atrial pacing had a similar effect on haemodynamics during KEE, except that pacing decreased RAP. In conclusion, the human heart can be paced to a higher HR than observed during maximal exercise, suggesting that HRmax and myocardial work capacity do not limit V ̇ O 2 max in healthy individuals. A limited left ventricular filling and possibly altered contractility reduce SV during atrial pacing, whereas a plateau in LVFP appears to restrict Q ̇ close to V ̇ O 2 max .